Pharmacogenomics to predict drug response. (1st February 2000) - Adam, Gail IR; Reneland, Richard; Andersson, Maria; Risinger, Carl; Nilsson, Mats; Lewander, Tommy
From theory to proof-of-concept, pharmacogenomics promises to improve future general healthcare in a number of ways. By identifying individuals who will respond to a particular drug treatment compared to those who have a low probability of response, pharmacogenomic test development hopes to aid the physician in prescribing the optimal medication for each patient. This approach promises faster relief from symptoms, a lowering of side effect risks and a reduction in healthcare costs. Pharmacogenomic tests used by the pharmaceutical companies themselves can be used to help identify suitable subjects for clinical trials, aid in interpretation of clinical trial results, find new markets for current products and speed up the development of new treatments and therapies. This type of approach should also see fewer compounds failing during later phases of development. The questions we are faced with as we enter the new millennium, however, are if and when the promises of pharmacogenomics in improving healthcare will be fulfilled. Currently, there are only a handful of pharmacogenomic tests and associated products which are commercially available and it remains to be seen what impact these will have on the market and on healthcare in general.